2022
DOI: 10.1038/s41586-022-05542-y
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and persistence in the human body and brain at autopsy

Abstract: Coronavirus disease 2019 (COVID-19) is known to cause multi-organ dysfunction 1 – 3 during acute infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), with some patients experiencing prolonged symptoms, termed post-acute sequelae of SARS-CoV-2 (refs. 4 , 5 ). However, the burden of infection outside the respiratory tract and time to viral clearance are not well characterized, parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
315
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 551 publications
(410 citation statements)
references
References 51 publications
11
315
1
2
Order By: Relevance
“…This appears driven partly by concerns about the persistence of SARS-CoV-2 viral RNA in the lung and extrapulmonary tissue, which can be detected for weeks to months after the initial diagnosis. 13 , 15 , 19 However, the detection of genomic RNA cannot differentiate replicating viruses from nonreplicating viruses, resulting in discard of organs that may not pose a risk of viral transmission. An assay capable of detecting active viral replication with high sensitivity could prove useful in further stratifying the risk of SARS-CoV-2 transmission from donors with a recent COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This appears driven partly by concerns about the persistence of SARS-CoV-2 viral RNA in the lung and extrapulmonary tissue, which can be detected for weeks to months after the initial diagnosis. 13 , 15 , 19 However, the detection of genomic RNA cannot differentiate replicating viruses from nonreplicating viruses, resulting in discard of organs that may not pose a risk of viral transmission. An assay capable of detecting active viral replication with high sensitivity could prove useful in further stratifying the risk of SARS-CoV-2 transmission from donors with a recent COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 proteins and RNA have, however, been identified in multiple organs, and data suggest that viral RNA can persist in tissues for prolonged periods of time following an infection. 14 , 15 In a scenario in which a donor with a recently resolved COVID-19 infection has an LRT sample positive for SARS-CoV-2 by genomic RNA testing, sgRNA testing of an LRT sample and of a bronchial tissue via transbronchial biopsy could be performed to assess replication-competent viruses and guide organ utilization decisions ( Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An outbreak of SARS-CoV-2 began in December 2019 and has infected hundreds of millions of people worldwide so far [5]. Meanwhile, this lethal virus may trigger a strong immune response in the host [6]. Thus, it would be very interesting to investigate if SARS-CoV-2 infection could enhance the host's antitumor immunity.…”
Section: Letter To the Editormentioning
confidence: 99%
“…The mechanism(s) whereby brain pathology/immunopathology and/or neuropathology might manifest in COVID-19 patients remains debatable, with the systemic cytokine storm and/or direct brain infection likely involved 22,[27][28][29][30][31][32] . A number of studies have now shown brain infection in COVID-19 patients [33][34][35][36][37] , with viral RNA or protein detected in the brains of 20-38% of patients that died of COVID-19 38,39 . A number of groups have also reported detection of viral RNA in cerebrospinal fluid of COVID-19 patients [40][41][42][43][44] , including patients infected with omicron virus 45 .…”
Section: Introductionmentioning
confidence: 99%